The association between cardiorespiratory fitness and performance in a submaximal stepping test standardised for external workload - Huchu, Linet (MRC/UCT RU for Exercise and Sport Medicine, 2017)
Submaximal step tests are used to predict maximal oxygen consumption and work capacity. However, if the external workload is not controlled the interpretation of the test results may be inaccurate. The purpose of the research was to develop a submaximal test of cardiorespiratory fitness using a novel step test designed specifically to overcome the weaknesses of the previously published step tests. A series of studies contributed to the theoretical development of the submaximal step protocol, piloting the protocol, reliability studies, validation of the protocol and finally a cross-validation of the protocol. The first study tested the hypothesis that stepping tests configured for the same external workload, but varying in stepping frequency, elicit the same physiological stress. Participants (n = 31) performed three step tests at 16, 20 and 24 steps per minutes in random order. External workload was standardised at 45 kJ. Energy expenditure, heart rate recovery, rating of perceived exertion, maximum heart rate and total heart beats were significantly different between tests (p < 0.05) with the biggest differences occurring between 16 and 24 steps per minute. Maximum heart rate as a percentage of age predicted heart rate increased from 70% at 16 steps per minute to 81% at 24 steps per minute. The study concluded that standardisation of external workload with different exercise intensities does not result in the same physiological responses. The second study tested the reliability of the step test. Participants (n = 34) performed a step test three times in a week at a cadence of their choice (16, 20 or 24 steps per minute). The study showed that the step test is repeatable for most variables measured and therefore is a reliable test of fitness. The third study used the outcome variables measured during the step test to develop equations which predicted VO₂max measured directly in a maximal test on a treadmill. A diverse sample of participants (n = 273), differing in sex, level of habitual physical activity and age were recruited for the study. Several models for predicting VO₂max were determined. The most parsimonious equation was: VO₂max (ml.kg⁻¹.min⁻¹) = -0.10911 (age) - 0.06178 (body mass) - 0.75481 (body fat %) +0.00208 (METS) + 0.11636 (HRR) - 0.019551 (MHR) + 0.07955 (Av HR) + 83.34846 (R² = 0.75, standard error of estimate = 5.51 ml.kg.min⁻¹) where METS is metabolic equivalent, HRR is heart rate recovery, MHR is maximum heart rate and Av HR is average heart rate. Cross validation was done (n = 50) to test the accuracy of the prediction equation. The relationship between the predicted VO₂max and the measured VO₂max was r = 0.87. In conclusion the standardised step test can predict VO₂max in a heterogeneous population of males and females, varied ages (20 to 60 years), physical activity levels and fitness levels.